Popular Economy of the City? Study of the family groups U6A and Nueva Generación, J. C. Mariátegui, San Juan de Lurigancho, Lima - Valdivieso Alvarado, Alejandro (2017)
Popular economy in the city? The current text tries to answer that by using a comparative analysis between two family aggrupation’s; U6A and Nueva Generacion located in the human settlement Jose Carlos Mariategui, San Juan de Lurigancho distritc, Lima city. For this purpose is mandatory the reconstruction of their memory, the visibilization of their organization and intern conflicts, their relationship with extern agents and last, their future perspectives.